Jak w Domu Oświatowym Bibliotekę Sejmu Śląskiego urządzano (PDF 1,56 MB) (Książnica Śląska, 2025)
In 1934 the Biblioteka Sejmu Śląskiego was moved to the buildingof the Dom Oświatowy on ulica Francuska 12. The article describes how the reading room, lending library and library warehouseswere arranged in a space not originally intended for a library. The textrecalls the most important events from 1933-1934 (e.g. the visit of thedirector of the Ossolineum Ludwik Bernacki), describes Jacek Koraszewski’s project, as well as the move and the new organization of thelibrary prepared by director Paweł Rybicki.